Microcontroller-Based Cigarette Smoke Detector and Neutralizer - Andi Ircham Hidayat; Nurkhalik Wahdanial Asbara (Jurnal E-Komtek, 2022)
Non-smoking areas in Indonesia are still very minimal, and if any, they may still be violated because the sanctions can be said to be non-existent. Some smokers do not understand the tolerance for the discomfort of passive smokers forced to smell cigarettes smoke: they must inhale the burnt smell of tobacco until they feel short of breath. Some sensitive passive smokers will cough right away. This study aims to design a device that can detect cigarette smoke by neutralizing it. The result of this study is that all tools made worked and functioned as expected, so they are expected to be used as a means of controlling cigarette smoke in a closed space. Raspberry Pi as the main controller is quite efficient because it requires a small power supply source.